Immunology‐Guided Biomaterial Design for Mucosal Cancer Vaccines. Issue 13 (13th December 2019) - Ferber, Shiran; Gonzalez, Rodrigo J.; Cryer, Alexander M.; von Andrian, Ulrich H.; Artzi, Natalie
Abstract: Cancer of mucosal tissues is a major cause of worldwide mortality for which only palliative treatments are available for patients with late‐stage disease. Engineered cancer vaccines offer a promising approach for inducing antitumor immunity. The route of vaccination plays a major role in dictating the migratory pattern of lymphocytes, and thus vaccine efficacy in mucosal tissues. Parenteral immunization, specifically subcutaneous and intramuscular, is the most common vaccination route. However, this induces marginal mucosal protection in the absence of tissue‐specific imprinting signals. To circumvent this, the mucosal route can be utilized, however degradative mucosal barriers must be overcome. Hence, vaccine administration route and selection of materials able to surmount transport barriers are important considerations in mucosal cancer vaccine design. Here, an overview of mucosal immunity in the context of cancer and mucosal cancer clinical trials is provided. Key considerations are described regarding the design of biomaterial‐based vaccines that will afford antitumor immune protection at mucosal surfaces, despite limited knowledge surrounding mucosal vaccination, particularly aided by biomaterials and mechanistic immune–material interactions. Finally, an outlook is given of how future biomaterial‐based mucosal cancer vaccines will be shaped by new discoveries in mucosal vaccinology, tumor immunology, immuno‐therapeutic screens, and material–immune system interplay. Abstract : Cancer of mucosal tissues is a major cause of worldwide mortality. Engineered cancer vaccines offer a promising approach for inducing antitumor immunity. Challenges associated with vaccination through mucosal and parenteral routes are discussed. Specifically, key considerations are described in the design of biomaterial‐based vaccines that will afford antitumor immune protection at mucosal surfaces.